1989
DOI: 10.1248/cpb.37.648
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic triterpenes from a chinese medicine, Goreishi.

Abstract: Bioactivity-guided fractionation of the methanol extract of Goreishi (the feces of Trogopterus xanthipes Milne-Edwards) afforded one new and three known cytotoxic triterpenes, namely, 3-O-cis-p-coumaroyltormentic acid, pomolic acid, 2 alpha-hydroxyursolic acid, and jacoumaric acid. In the course of this investigation, six additional compounds having no cytotoxic activity were isolated, namely, maslinic acid, 3-O-trans-p-coumaroylmaslinic acid, ursolic acid, tormentic acid, euscaphic acid, and a new triterpene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(89 citation statements)
references
References 0 publications
3
83
0
3
Order By: Relevance
“…3β-Acetoxy-ursolic acid (103) was also antimutagenic in the umu test (Miyazawa et al, 2005) and had antitumor activity in vivo (Dominic and Subbaiyan, 1993) and some aromatase-inhibiting activity in vitro (Jeong et al, 2000). Although 2α-hydroxy-ursolic acid (104) inhibited TPA-induced EBV-EA (Banno et al, 2004) and showed good cytotoxicity to several cancer cell lines, seeming to be particularly effective against solid tumors Numata et al, 1989;Ahn et al, 1998;El-Hossary et al, 2000;Kim et al, 2000), in one study it was as cytotoxic to normal human fibroblasts as to two tumor cell lines (Taniguchi et al, 2002). The cytotoxicity seems to be related to the compound's ability to inhibit protein kinase C (EC 2.7.11.13) (Ahn et al, 1998).…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…3β-Acetoxy-ursolic acid (103) was also antimutagenic in the umu test (Miyazawa et al, 2005) and had antitumor activity in vivo (Dominic and Subbaiyan, 1993) and some aromatase-inhibiting activity in vitro (Jeong et al, 2000). Although 2α-hydroxy-ursolic acid (104) inhibited TPA-induced EBV-EA (Banno et al, 2004) and showed good cytotoxicity to several cancer cell lines, seeming to be particularly effective against solid tumors Numata et al, 1989;Ahn et al, 1998;El-Hossary et al, 2000;Kim et al, 2000), in one study it was as cytotoxic to normal human fibroblasts as to two tumor cell lines (Taniguchi et al, 2002). The cytotoxicity seems to be related to the compound's ability to inhibit protein kinase C (EC 2.7.11.13) (Ahn et al, 1998).…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…5) Since no systematic work has so far been reported on the lipophilic constituents of perilla leaves with potential biological activities, we were particularly interested in examining these compounds for their potential antitumor-promoting and anti-inflammatory activities. We report in this paper the isolation and identification of nine triterpene carboxylic acids (1)(2)(3)(4)(5)(6)(7)(8)(9) from the ethanol (EtOH) extracts of red and green perilla leaves and their inhibitory effects on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced inflammation in mice, and on the Epstein-Barr virus early antigen (EBV-EA) activation induced by TPA. In addition, we report the inhibitory effect of tormentic acid (5) on in vivo two-stage mouse skin carcinognenesis.…”
mentioning
confidence: 99%
“…(Table 1) and DEPT spectra of 2 showed thirty carbons, including seven methyls, eight methylenes, six methines, and nine quaternary signals. These data, together with the analysis of 1 H-1 H COSY and HMBC spectra suggested that 2 possessed an ursane-type skeleton, and was structurally related with ursolic acid [4]. The differences between 2 and ursolic acid were mainly in ring B.…”
Section: Introductionmentioning
confidence: 78%
“…possesses an oleanane-type skeleton [3]. Comparison of the NMR data of 1 with those of maslinic acid and 3β-acetoxy-11α,13β-dihydroxyolean-12-one [4,5] disclosed that the two olefinic carbons in maslinic acid were replaced by an oxygenated quaternary carbon at δ 90.0 and a ketone group at δ 200.2, besides, in 1 an oxygen-bearing methine at δ 56.1 was observed, instead of a methylene found in maslinic acid. The 1 H-1 H COSY coupling of H-9 (δ 2.16) with H-11 (δ 4.31), together with HMBC correlations from H-9 and H-11 to C-12 (δ 200.2), from H-11, Me-27 (δ 1.38), and H-19 (δ 1.82/1.42) to C-13 (δ 90.0) suggested that a ketone was positioned at C-12, and C-11 and C-13 were oxygenated, respectively.…”
Section: Introductionmentioning
confidence: 99%